If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -6x = 0 Combine like terms: -6x + -6x = -12x -12x = 0 Solving -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-12'. x = 0 Simplifying x = 0
| 8(-4h+10)=-16-2(19h-15) | | 9p=-7(-2p+3)-4 | | -7.2r+12.13=17.05-3.1r | | 2-(7-2v)=25-3v | | 5(a-8)=40 | | x/72=8/9 | | 3b+4b-6=15 | | -24=8r | | 5.4(3k-12)+3.3(2k+6)=-136 | | 19x+x= | | 20x^3-3x^2-9x=0 | | 2(u+3v)=w-5u | | 9x-14=6x+17 | | h=7(3.14)m | | 0.2(x+50)= | | 4+3(x-1)=511 | | -15.6g+20=-16.8g+4.9+3.94 | | -15.6g+20=-16.8g*4.9+3.94 | | 4(2-5)=12 | | 9x^2-y^2=9 | | (10*x)-25=75 | | 2n-(n-5)=17 | | -4(p-2)-5p=-22-4p | | 4(3-5)=12 | | 2n+7n^3+7n^3-3n^4+7n^3-3n^4= | | 6x-8y=3 | | 3x^2+16y-12= | | 27x^3-129x=0 | | -9+x=-2(-2x-6) | | (2x+5)=11 | | -1+5(2x-3)=16x-2(3x+8) | | (x^2)-x=2 |